2021
DOI: 10.1186/s40478-020-01106-1
|View full text |Cite
|
Sign up to set email alerts
|

The administration of antisense oligonucleotide golodirsen reduces pathological regeneration in patients with Duchenne muscular dystrophy

Abstract: During the last decade, multiple clinical trials for Duchenne muscular dystrophy (DMD) have focused on the induction of dystrophin expression using different strategies. Many of these trials have reported a clear increase in dystrophin protein following treatment. However, the low levels of the induced dystrophin protein have raised questions on its functionality. In our present study, using an unbiased, high-throughput digital image analysis platform, we assessed markers of regeneration and levels of dystroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…2C ) [ 22 ], and that myofiber regeneration decreased after golodirsen treatment, indicated by fewer fibers positive for fetal/developmental myosin at week 48 compared with baseline ( Fig. 2D ) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2C ) [ 22 ], and that myofiber regeneration decreased after golodirsen treatment, indicated by fewer fibers positive for fetal/developmental myosin at week 48 compared with baseline ( Fig. 2D ) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have also demonstrated the molecular functionality of dystrophin protein produced by DMD myotubes after golodirsen treatment [ 24 ]. Consistently, we have previously demonstrated in post-treatment biopsy data from golodirsen-treated patients that increased dystrophin was associated with a 2.2% decrease in fibers positive for the regeneration marker fetal/developmental myosin [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“… 23 This study was initially planned to pave the way for a clinical trial in this population. 24 Given the approval of golodirsen, an antisense oligonucleotide that induces skipping of exon 53, 25 , 26 and the development of other therapies with similar modes of action, the present set of data offers the opportunity to benchmark treated patients with natural history of patients with the same genotype.…”
Section: Discussionmentioning
confidence: 99%
“…This drug behaves similarly to eteplirsen, in that it enables exon skipping; however, it leads to the exclusion of exon 53 instead of exon 51 [ 114 ]. This results in functional dystrophin and improves symptomology of patients with DMD caused by mutations that are acquiescent to exon 53 skipping [ 19 ].…”
Section: Rna Therapeuticsmentioning
confidence: 99%